Effect of Well Pattern to the Water Alternating Gas (WAG) Carbon Dioxide Injection on Angsi 1-35 Reservoir - Ahmad Ruslan, Ahmad Ehsan (Universiti Teknologi Petronas, 2008)
This work presents the effect of different well pattern on the Water-alternating-gas (WAG) carbon dioxide injection for Angsi 1-35 reservoir in offshore Terengganu. The use of WAG C02 injection seems to be the most promising option as enhanced oil recovery method for Angsi 1-35 field. This work focuses on the five typical well patterns: five-spot, seven-spot, inverted seven-spot, direct line drive and staggered line drive. The prediction of oil recovery for each of the pattern was conducted using simple theoretical calculations, which are based on the sweep efficiency equation, and by using numerical simulations. The results obtained from both methods were compared in order to identify the well pattern that gives the highest recovery. It was found that inverted seven-spot pattern yields the highest oil recovery of 52%, which was about 12% more from the current recovery under natural production. The cost incurred by employing different well patterns was also analysed. The most profitable well pattern was the inverted seven-spot which gives the highest percentage of internal rate return (IRR) at 96.91% and the least profitable option was seven spot well patterns as it laid the lowest percentage of IRR at 53.79%. Cost analysis confirmed that all well patterns offered good results in term of profitability as all of them exceeded the minimum attractive IRR limit which is at 30%, hence proving that all the five well patterns are feasible to be conducted.